Pegadaian Sharia In The Successful Development Of Msmes Through Arrum BPKB (Case Study Of Pegadaian Sharia CPS Ar Hakim Medan) - Siregar, Rihadatul 'Aisy Arifah; Hutagalung, Arif Qaedi; Dilham, Ami; Qamariah, Inneke (Journal Of Management Analytical and Solution (JoMAS), 2023)
This study aims to determine the Sharia Pegadaian in the Success of BPKB ARRUM Development. Study of Islamic Pawnshops CPS AR Hakim Medan. This research is a mixed research method with a concurrent embedded design by combining two types of research, qualitative as the primary method and quantitative as a secondary or complementary method. Data collection through interviews and questionnaires. The informants in this study totaled 15 people consisting of 3 employees of the CPS AR Hakim Sharia Pawnshop, 10 customers or business actors, and 2 Heads of Environment around micro business actors including customers who use ARRUM BPKB products at the CPS AR Hakim Sharia Pawnshop in 2020 with determination sample using purposive sampling. The results of the study show that sharia pawnshops can succeed in the development of MSMEs through ARRUM BPKB financing with educated customers and relief for restructuring customers. You can see an increase in business turnover, business assets, net income, production levels, and consumer levels between before and after using ARRUM BPKB CPS AR financing Medan Judge.